β-adrenergic signaling triggers enteric glial reactivity and acute enteric gliosis during surgery - Patrick Leven; Reiner Schneider; Linda Schneider; Shilpashree Mallesh; Pieter Vanden Berghe; Philipp Sasse; Jörg C. Kalff; Sven Wehner (Journal of Neuroinflammation, 2023)
Abstract Background Enteric glia contribute to the pathophysiology of various intestinal immune-driven diseases, such as postoperative ileus (POI), a motility disorder and common complication after abdominal surgery. Enteric gliosis of the intestinal muscularis externa (ME) has been identified as part of POI development. However, the glia-restricted responses and activation mechanisms are poorly understood. The sympathetic nervous system becomes rapidly activated by abdominal surgery. It modulates intestinal immunity, innervates all intestinal layers, and directly interfaces with enteric glia. We hypothesized that sympathetic innervation controls enteric glia reactivity in response to surgical trauma. Methods Sox10 iCreERT2 /Rpl22 HA/+ mice were subjected to a mouse model of laparotomy or intestinal manipulation to induce POI. Histological, protein, and transcriptomic analyses were performed to analyze glia-specific responses. Interactions between the sympathetic nervous system and enteric glia were studied in mice chemically depleted of TH+ sympathetic neurons and glial-restricted Sox10 iCreERT2 /JellyOP fl/+ /Rpl22 HA/+ mice, allowing optogenetic stimulation of β-adrenergic downstream signaling and glial-specific transcriptome analyses. A laparotomy model was used to study the effect of sympathetic signaling on enteric glia in the absence of intestinal manipulation. Mechanistic studies included adrenergic receptor expression profiling in vivo and in vitro and adrenergic agonism treatments of primary enteric glial cell cultures to elucidate the role of sympathetic signaling in acute enteric gliosis and POI. Results With ~ 4000 differentially expressed genes, the most substantial enteric glia response occurs early after intestinal manipulation. During POI, enteric glia switch into a reactive state and continuously shape their microenvironment by releasing inflammatory and migratory factors. Sympathetic denervation reduced the inflammatory response of enteric glia in the early postoperative phase. Optogenetic and pharmacological stimulation of β-adrenergic downstream signaling triggered enteric glial reactivity. Finally, distinct adrenergic agonists revealed β-1/2 adrenoceptors as the molecular targets of sympathetic–driven enteric glial reactivity. Conclusions Enteric glia act as early responders during post-traumatic intestinal injury and inflammation. Intact sympathetic innervation and active β-adrenergic receptor signaling in enteric glia is a trigger of the immediate glial postoperative inflammatory response. With immune-activating cues originating from the sympathetic nervous system as early as the initial surgical incision, adrenergic signaling in enteric glia presents a promising target for preventing POI development.